HAK ASUH ANAK PADA PERCERAIAN PUBLIK FIGUR: ANALISIS KOMPARATIF HUKUM PERDATA DAN HUKUM ISLAM DI INDONESIA - Revi Inayatillah (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2026)
Divorce among public figures is often colored by complicated child custody disputes (hadhanah) and receives massive media attention. This normative juridical research with a comparative approach analyzes the settlement of child custody disputes according to Civil Law (Civil Code and Marriage Law) and Islamic Law (Compilation of Islamic Law), by highlighting the influence of public figure status on judges' considerations. The results of the study show that both legal systems prioritize the principle of the best interests of the child. However, its implementation in the case of public figures is often faced with the complexity of media exposure, lifestyle, and emotional stability of parents. In terms of regulation, Islamic Law provides more rigid guidelines regarding the order of custody holders based on the age of the child (including mumayyiz status), while Civil Law provides broader discretion for judges to objectively assess the abilities of parents without rigid age limits.